The effect of temperature on dengue virus transmission by Aedes mosquitoes - Liu, Zhuanzhuan; Zhang, Qingxin; Li, Liya; He, Junjie; Guo, Jinyang; Wang, Zichen; Huang, Yige; Xi, Zimeng; Yuan, Fei; Li, Yiji; Li, Tingting (Frontiers in Cellular and Infection Microbiology, 2023)
Dengue is prevalent in tropical and subtropical regions. As an arbovirus disease, it is mainly transmitted by Aedes aegypti and Aedes albopictus. According to the previous studies, temperature is closely related to the survival of Aedes mosquitoes, the proliferation of dengue virus (DENV) and the vector competence of Aedes to transmit DENV. This review describes the correlations between temperature and dengue epidemics, and explores the potential reasons including the distribution and development of Aedes mosquitoes, the structure of DENV, and the vector competence of Aedes mosquitoes. In addition, the immune and metabolic mechanism are discussed on how temperature affects the vector competence of Aedes mosquitoes to transmit DENV.